Materiality, meanings, and competences for historic rural buildings: a social practice approach for engaging local communities in energy transition. Issue 1 (October 2021) - Balest, J.; Lucchi, E.; Haas, F.; Grazia, G.; Exner, D
Abstract: Natural and cultural heritage are important resources for engaging local communities in the promotion of a sustainable future, both for achieving energy targets and repopulating rural areas. Public engagement is an important factor particularly to preserve historic rural buildings and its landscapes in Alpine communities, where people build up an emotional relationship with cultural and natural heritage. The study, realised in the framework of the Interreg ITA-AUT SHELTER project, aims at defining a new use for an abandoned historical building by the engagement of the local community and, according to the new use, at defining insights for elaborating the energy retrofit balancing preservation and sustainability issues. The study also identifies the relevant elements to be available within a local community to ensure a long-lasting use and management of a public retrofitted historical building. Among these elements and using the sociological lens, we investigate: the materiality of the historic building and its landscape; the community and social meanings attributed to the building and the landscape; and the heritage management competences of the local community to manage and maintain the building in the next future. All these elements can be translated into a social practice of building and land management that avoids a second abandonment. Social science-based interviews are conducted in Valbrenta (IT), using content analysis.